2013
DOI: 10.5603/fhc.2013.007
|View full text |Cite
|
Sign up to set email alerts
|

Galanin immunoreactivity in the brain of the desert lizard Uromastyx acanthinura during activity season

Abstract: Abstract:The distribution of galanin immunoreactive perikarya and nerve fibers in the brain of the desert lizard U. acanthinura was studied by means of immunofluorescence using an antiserum against rabbit galanin. The animals were captured during the activity season in March (wet season) just before reproduction period and in June (arid season) after ovulation period. Immunoreactive neurons were mostly detected in the mediobasal and the infundibular recess nuclei, the nucleus of the paraventricular organ, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Some of the preoptic galanin neurons may express gonadotropin-releasing hormone (Rossmanith et al 1996). However, it has often been reported that the expression of galanin may be conditional, and depend on sex, hormonal background, and other factors in different hypothalamic neurons in various species (Christiansen 2011; Diaz-Cabiale et al 2014; Garcia-Falgueras et al 2011; Hammouche and Bennis 2013; Porteous et al 2011; Tillet et al 2012; Whitelaw et al 2012). Therefore, the possibility exists that the difference between the distribution of galanin in rats and mice could be a consequence of conditions apart from the species difference.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the preoptic galanin neurons may express gonadotropin-releasing hormone (Rossmanith et al 1996). However, it has often been reported that the expression of galanin may be conditional, and depend on sex, hormonal background, and other factors in different hypothalamic neurons in various species (Christiansen 2011; Diaz-Cabiale et al 2014; Garcia-Falgueras et al 2011; Hammouche and Bennis 2013; Porteous et al 2011; Tillet et al 2012; Whitelaw et al 2012). Therefore, the possibility exists that the difference between the distribution of galanin in rats and mice could be a consequence of conditions apart from the species difference.…”
Section: Discussionmentioning
confidence: 99%